2009
DOI: 10.1029/2008ja013730
|View full text |Cite
|
Sign up to set email alerts
|

The decay phase of solar energetic particle events

Abstract: [1] The shape of the particle flux profile in the decay phase of solar energetic particle (SEP) events is of particular importance in understanding the propagation of energetic particles in the interplanetary medium. The majority of few-MeV proton events (>90%) exhibit exponential law declines, suggesting the dominant role of convection transport and adiabatic deceleration. In this case, the characteristic decay time t should depend on the spectral index, the solar wind speed, and the distance from the Sun. Mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
24
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(29 citation statements)
references
References 33 publications
2
24
2
Order By: Relevance
“…Statistical studies of the decay phase of SEP events have been mostly focused on proton observations (e.g., Daibog et al 2003;Kecskeméty et al 2009, and references therein). Daibog et al (2003), on a sample of ∼700 events collected during almost three solar cycles, concluded that in nearly 90% of the cases for 1-5 MeV proton fluxes, an exponential decay gives the best approximation to the time-intensity profiles.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Statistical studies of the decay phase of SEP events have been mostly focused on proton observations (e.g., Daibog et al 2003;Kecskeméty et al 2009, and references therein). Daibog et al (2003), on a sample of ∼700 events collected during almost three solar cycles, concluded that in nearly 90% of the cases for 1-5 MeV proton fluxes, an exponential decay gives the best approximation to the time-intensity profiles.…”
Section: Introductionmentioning
confidence: 99%
“…The most recent study on the decay rate of SEP events was performed by Kecskeméty et al (2009). These authors studied the decay phase of 0.5-48 MeV proton events observed by the Interplanetary Monitor Platform (IMP-8) near the ecliptic at ∼1 AU from the Sun between 1973 and 2001.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Regarding SEP duration prediction, few studies (e.g. Kahler 2005;Kecskemety et al 2009) have been carried out on the downstream (post-shock) region, mostly discussing the dependences between the characteristic decay time and several solar and interplanetary factors (e.g. heliolongitude of the solar parent event, CME properties, particle energy of accelerated particles, solar wind conditions).…”
Section: Introductionmentioning
confidence: 99%